Efek Higiene Sanitasi Terhadap Infeksi Kecacingan pada Anak SD - Aisah Rahmawati (Poltekkes Kemenkes Semarang, 2019)
Soil Transmitted Helminths (STH) is a transmitted intestinal nematode through the soil. Primary school children (SD) have a high risk due to several factors which one is the low level of personal sanitation hygiene. Elementary school children Bedug 03 have a habit of not washing hands before eating, not maintaining hygiene after defecation, uncontrolled hand hygiene, and children's habits of playing in dirty places and not wearing footwear. To find out whether there is relation of Sanitation Hygiene with Worms Infection In SDN Bedug 03 Pangkah Subdistrict, Tegal Regency. This is a descriptive explanative research using a cross sectional approach. The number of sample is 96 children. The feces sample is collected and examined through qualitative direct method. The occurence of Soil Transmitted Helmints worm’s egg infection with the result of 14 children (14,6%) are positive of Ascaris lumbricoides worm’s egg, 1 children (1,04%) is positive of the double of Ascaris lumbricoides and hookworm’s egg, 1 children (1,04%) are positive of hookworm’s egg, 1 children (1,04%) are positive of Trichuris trichiura worm’s egg and 79 children (82,3%) are negative of worm’s egg. The Sanitation Hygiene behavior in elementary school children Bedug 03 is 63 children (65,6%) gain good result and 33 children (34,4%) gain bad result. There is relation of Sanitation Hygiene with Worms Infection In SDN Bedug 03 Pangkah Subdistrict, Tegal Regency.